2021
DOI: 10.1177/1045389x20987002
|View full text |Cite
|
Sign up to set email alerts
|

Leakage detection of water pipelines based on active thermometry and FBG based quasi-distributed fiber optic temperature sensing

Abstract: Water pipelines are the efficient and reliable way for water transportation. Leakage of pipelines can lead to tremendous waste of water resources and large economic loss. In this paper, a novel leakage detection method was proposed based on active thermometry and fiber Bragg grating (FBG) based quasi-distributed fiber optic temperature sensing. In this method, the thermal sensing cable was fabricated by coupling heating cable with quasi-distributed temperature sensors. The heat was introduced by the heating ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Moreover, fiber optic‐based leak detection include two types of systems on basis of their design: discrete and distributed. The discrete system mainly uses a single fiber optic sensor focuses on collecting point data from a single point at a time (Li et al, 2021). In contrast, the distributed system consists of multiple sensors which can make multiple measurements simultaneously (Muanenda et al, 2019).…”
Section: Current Technologies For Leak Detection and Localizationmentioning
confidence: 99%
“…Moreover, fiber optic‐based leak detection include two types of systems on basis of their design: discrete and distributed. The discrete system mainly uses a single fiber optic sensor focuses on collecting point data from a single point at a time (Li et al, 2021). In contrast, the distributed system consists of multiple sensors which can make multiple measurements simultaneously (Muanenda et al, 2019).…”
Section: Current Technologies For Leak Detection and Localizationmentioning
confidence: 99%
“…On the basis of the monitoring scheme, the fiber-optic sensors can be classified as discrete and distributed. A discrete scheme allows measurement at a single point and mainly uses fiber Bragg grating as the sensing material whose center wavelength changes with temperature or strain variation (Li et al 2021). A number of fiber Bragg gratings are inscribed on various distances over the same fiber for long-distance sensing.…”
Section: Fiber Optics Technologymentioning
confidence: 99%
“…The literature review revealed that most of the studies adopted distributed optical fibre sensors (DOFS) sensing mechanism for leak detection and localization (Nikles et al 2004;Li et al 2021;Yao et al 2021). Research demonstrating other available fiber optics sensing systems for leak detection is limited and their potential of higher efficiency and cost-effectiveness is less explored.…”
Section: Research On Mitigating High Cost Deployment and Maintenance Issuesmentioning
confidence: 99%
“…Therefore, they can detect large leakage hole or deformation, but not all types of leakage points. Besides the above engineering logging techniques, distributed fiber acoustic sensing (DAS) 42,43 and distributed fiber temperature sensing (DTS) 44 can also measure the leakage noise and temperature difference, but the fiber cannot reach a depth over 4500 m due to limited tensile strength. Therefore, it is not suitable for the leakage measurement in high‐pressure well, because the high‐pressure well is usually over 5000 m depth 45–47 …”
Section: Introductionmentioning
confidence: 99%